Penyuluhan Kesehatan Tentang Manfaat Massage Pada Bayi di Wilayah Kerja Puskesmas Palimanan - Sumarmi Sumarmi; Erida Fadilah (Pusat Riset dan Inovasi Nasional, 2023)
In infancy, to have an optimal body the baby needs sufficient time. 36 months. People say, this is the golden age, this period is considered an important period because at this time babies are still very sensitive to the environment and need to be given sufficient nutrition and stimulation to grow and develop (Ministry of Health of the Republic of Indonesia, 2009). Growth and development Childhood is an understanding of the complex processes in which children develop and grow physically, cognitively, socially, and emotionally during their growth years. The aim of this activity is to apply baby massage therapy correctly as an initial effort to stimulate the baby's growth and development, especially to increase body weight. The method used is health education which is carried out by means of lectures, discussions and questions and answers about baby massage material including the benefits, methods and growth and development of children as well as checking the baby's weight, height and stage of development. This activity was attended by 34 mothers with toddlers and posyandu cadres in Ciawi Village, District. Palimanan and its female cadres. The response from posyandu cadres to this activity was very good because they felt helped by community service activities like this.